2020
DOI: 10.3390/sym12122117
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level P2P Traffic Classification Using Heuristic and Statistical-Based Techniques: A Hybrid Approach

Abstract: Peer-to-peer (P2P) applications have been popular among users for more than a decade. They consume a lot of network bandwidth, due to the fact that network administrators face several issues such as congestion, security, managing resources, etc. Hence, its accurate classification will allow them to maintain a Quality of Service for various applications. Conventional classification techniques, i.e., port-based and payload-based techniques alone, have proved ineffective in accurately classifying P2P traffic as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Cao et al [25] developed an improved network traffic classification model based on SVM, achieving higher classification accuracy, 97.20%. Bhatia et al [26] proposed a DT-based multi-level P2P traffic classification technique based on packet and flow characteristics, achieving a combined accuracy rate of 98.30%. Dey et al [27] compared the performance of several ML models, including DT, RF, and artificial neural networks (ANNs), to classify network traffic and found that DT, RF, and ANNs achieved the best accuracy.…”
Section: Ml-based Network Traffic Classificationmentioning
confidence: 99%
“…Cao et al [25] developed an improved network traffic classification model based on SVM, achieving higher classification accuracy, 97.20%. Bhatia et al [26] proposed a DT-based multi-level P2P traffic classification technique based on packet and flow characteristics, achieving a combined accuracy rate of 98.30%. Dey et al [27] compared the performance of several ML models, including DT, RF, and artificial neural networks (ANNs), to classify network traffic and found that DT, RF, and ANNs achieved the best accuracy.…”
Section: Ml-based Network Traffic Classificationmentioning
confidence: 99%
“…On the same dataset over VPN tunnels, they achieved a recall of about 88% using the C4.5 algorithm. The literature [18] proposed a multi-level P2P traffic classification technique using C4.5 decision trees and statistical features of flows for P2P classification, which was also applicable to encrypted traffic. Similarly, there is literature [19,20] that used machine learning (KNN, SVM) for fine-grained classification of encrypted traffic classification.…”
Section: Related Workmentioning
confidence: 99%
“…Encrypted traffic identification task [11], whose purpose is to classify traffic into encrypted and non-encrypted traffic; • Service identification task, whose aim is to identify the service type of various applications to which the traffic belongs, such as chat applications, file transfer applications, etc. ; • Traffic application identification task [9,12], whose aim is to identify the concrete applications to which the traffic belongs, such as Youtube, Gmail, etc. ;…”
mentioning
confidence: 99%